2002
DOI: 10.1211/002235702405
|View full text |Cite
|
Sign up to set email alerts
|

Rapid inhibition of the contraction of rat tail artery by progesterone is mediated by inhibition of calcium currents

Abstract: Progesterone induced rapid relaxation of KCl-contracted tail artery helical strips from rats. The effect was dose dependent, with an IC50 (inhibitory concentration which produces 50% of the maximal response) of 8.9 microM progesterone. The actions of progesterone were not blocked by bicuculline, indicating that in this tissue the non-genomic actions of progesterone were not mediated via a gamma-aminobutyric acid (GABA)-A receptor. Fura-2 was used to measure intracellular calcium levels ([Ca(2+)](i)) in isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Our results showed a more powerful effect of PRG than βES at high concentrations (100 μmol/L). The inhibition of LTCC current by PRG in A7r5 cells is here reported for the first time, although Zhang et al observed in rat tail vascular smooth muscle cells that PRG reduced the LTCC [25] . We already studied the effect of PRG and βES on the BAY-stimulated I Ca,L .…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Our results showed a more powerful effect of PRG than βES at high concentrations (100 μmol/L). The inhibition of LTCC current by PRG in A7r5 cells is here reported for the first time, although Zhang et al observed in rat tail vascular smooth muscle cells that PRG reduced the LTCC [25] . We already studied the effect of PRG and βES on the BAY-stimulated I Ca,L .…”
Section: Discussionsupporting
confidence: 40%
“…[20] . Some authors showed that the inhibition of Ca 2+ channels is associated to the vasodilatation mediated by estrogens [21][22][23] and PRG [24,25] . The effects of βES and PRG on VOCCs were the objective of some studies.…”
Section: Centro De Investigação Em Ciências Da Saúde Universidade Damentioning
confidence: 99%
“…Thus, the vasorelaxing effect to sex steroids could be due, at least in part, to inhibition of L-type Ca 2+ channels (Zhang et al, 1994(Zhang et al, , 2002Scragg et al, 2004) and/or activation of K + channels (Deenadayalu et al, 2001). However, our results showing that steroids-induced vasorelaxation was not affected by inhibitors of BK Ca , K v and K ATP channels rules out the involvement of K + channels.…”
Section: Potential Mechanisms Involved In the Mode Of Action Of Steromentioning
confidence: 54%
“…This is, to the best of our knowledge, the first functional line of evidence describing the relaxant effects of 5-reduced androgens and progestins on vascular tone of HUA which may represent a potential regulatory role on fetoplacental blood flow. Accordingly, other studies have also reported the vasorelaxing properties of female and male sex steroids in experimental animals (Mendelsohn and Karas, 1999;Zhang et al, 2002;Perusquía, 2003). Likewise, μM concentrations of 17β-estradiol and progesterone induce a vasorelaxing effect in the isolated human coronary, mammary, placental and omental arteries (Omar et al, 1995;Belfort et al, 1996;Mugge et al, 1997;Ramírez et al, 1998).…”
Section: Generalmentioning
confidence: 93%
See 1 more Smart Citation